Science parks as mechanism to enhance the development of a knowledge-based economy in Mozambique - Mhula, Alexandra Luis (University of the Western Cape, 2015)
Magister Economicae - MEcon === The 21st century marked the beginning of an era in which countries became increasingly dependent on information and communication technology (ICT). Technological change has not only become one of the key contributors to economic growth, it is also regarded as an essential element to enhance the general welfare of society (Hu, 2006). Not surprisingly, even governments of developing countries undertake various activities aimed at internalising the positive external impact of technological innovation in order to enhance the development of knowledge-based economies. Examples are the provision of basic information services, such as telephone- and internet services as well as distance learning technologies to make education more generally accessible. Another instrument that recently gained worldwide interest is the development of science parks, also known as information technology (IT) parks, techno parks or cyber parks. The rationale is to promote technological change, regional and/or urban development and to facilitate the diffusion of knowledge and technology through the establishment of knowledge networks. In 2004 there were approximately 600 science parks in the world, 70 percent of which were situated in the United States of America, Europe and Asia, but there is a growing trend towards its establishment in developing countries. However, the financing of such mega-projects in developing countries is especially problematic. A science park can be provided as a pure public project or pure private or through public-private partnerships (PPPs). Pure public financing is usually found in countries that have strong public sectors, such as China and India. On the other hand, in countries with well-developed private sectors they are mostly privately financed. In the case of most developing countries, private sectors are generally not developed enough and the public sectors cannot afford to finance projects of such a nature on a sustainable basis. These countries have no other option but to investigate the possibility of some other variation of a public-private-partnership (PPP) model.The Mozambican government acknowledges the urgency to enhance the development of a knowledge based economy and regards the establishment of a science park as a necessary policy intervention to provide the institutional basis for the diffusion of technological and communication innovation. As a result the country launched its first science park, to be developed in different stages, in 2008. But the real challenge for Mozambique lies in the financing of the park. It was estimated that only the first phase will require about 25 million USD. These funds were secured from the Indian government in the form of a loan. However, the government of Mozambique relies to a large extent on foreign aid to balance the national budget and there are no surplus funds to secure the sustainability of a project of such magnitude. This study firstly explored the economic rationale behind the establishment of a knowledgebased economy and the development of ICT. It then focused on science parks as institutions to secure the diffusion of technological innovation in Mozambique and also on empirical evidence from countries that have benefited greatly from investment in science park projects. The study also investigated the possibility to use a PPP-type of project to finance the science park in Mozambique and pointed out very important determinants for the successful implementation of PPP-projects. The study showed that the government of Mozambique is serious in its efforts to develop a knowledge-based economy although many projects are still in their 'infant' stages. It is strongly recommended that policy makers in Mozambique should study the outcomes of empirical research on various science parks projects in other developing countries. The study shows that Brazil seems to be successful in its use of a PPP for the country's science parks. Policy makers should also pay careful attention to other PPP-projects in Mozambique. Although they are mostly used for infrastructural projects, some failed, while others seem to be functioning efficiently and important lessons can be derived.